“O professor da nação” : Pedro Calmon e as crônicas para a seção segredos e revelações da história do Brasil na revista “O cruzeiro” entre 1960 e 1969 - Coutinho, Mariana Canazaro (2023)
In 1960, Pedro Calmon took on the section “Secrets and Revelations of the History of Brazil”, in the magazine “O Cruzeiro”, and started, then, to write to the great public about the past of the country. Between 1960 and 1969, Calmon wrote 338 chronicles. Our objective in this study is to analyze these chronicles, investigate the elements presented by the historian, the speech he used, and the fact that he maintained the writing of history in the journalistic field, besides the feeling of pride for the homeland he passed onto his readers. Therefore, in this study it was possible to observe that Calmon placed himself in this space as a true “Teacher of the Nation”. The historian brought to his chronicles a civic-patriotic speech when using elements of History to bring to his readers an optimist and harmonic view of the past of the country, making sure that his narrative showed the pride one should have for the Brazilian nation.